2016
DOI: 10.1021/acs.cgd.6b00150
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Aspects of Strain Relaxation and Compensation in InGaAs Metamorphic Structures Grown by MOVPE

Abstract: We present a selection of stack designs for MOVPE grown In x Ga 1−x As metamorphic buffer layers following various convex-down compositional continuous gradients of the In content, showing that defect generation and strain can be managed in a variety of ways, some rather unexpected (and unreported). Indeed, we observe that it is possible to grow surprisingly thick tensile strained layers on metamorphic substrates, without significant relaxation and defect generation. We believe our findings give significant in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Increasing the thickness of the AlInGaAs layer led to a higher RMS value, from ∼11 nm for the 300 nm thick layer to ∼23 nm for the AlInGaAs layer of 1400 nm thick preceded by an InGaAs strain-balancing layer. Indeed, the attempted addition of a strain-balancing layer before AlInGaAs layer deposition did not improve the surface roughness, despite showing promising results in previous works (ref ). Furthermore, the AlInGaAs compound showed a deteriorated surface with the subsequent deposition of other similar or thicker AlInGaAs layers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the thickness of the AlInGaAs layer led to a higher RMS value, from ∼11 nm for the 300 nm thick layer to ∼23 nm for the AlInGaAs layer of 1400 nm thick preceded by an InGaAs strain-balancing layer. Indeed, the attempted addition of a strain-balancing layer before AlInGaAs layer deposition did not improve the surface roughness, despite showing promising results in previous works (ref ). Furthermore, the AlInGaAs compound showed a deteriorated surface with the subsequent deposition of other similar or thicker AlInGaAs layers.…”
Section: Resultsmentioning
confidence: 99%
“…The In x Ga 1– x As MBL was deposited on the GaAs buffer following a single parabolic grading profile. The design, based on a model discussed in ref , was optimized as reported in ref . The STEM HAADF image of the full laser structure (Figure b) confirmed that most of the threading dislocation network was buried down close to the GaAs substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different chemical grading types of MB including uniform [ 15 17 ], step graded [ 18 20 ] and continuously graded [ 21 23 ]. The continuously graded approach could be linear [ 20 , 24 ] or parabolic [ 25 , 26 ], and generally speaking it allows more flexibility in the growth, tailoring the strain relaxation. Importantly, the parabolic profile has been shown to be less sensitive to variations in the MB thickness [ 22 ] and it has been shown to confine the defects further away from the active region [ 27 , 28 ] thus, making it a more promising approach for strain tuneability.…”
Section: Introductionmentioning
confidence: 99%
“…In recent experimental work, Gocalinska et al [14] considered InGaAs/GaAs (001) stacked heterostructures consisting of combinations of uniform and parabolically-graded layers. The objective of their work was to understand strain relaxation by adjusting the nominal compositional value and/ or thickness of the buffer layer for the purpose of controlling the strain and defect densities in the device layer.…”
Section: Introductionmentioning
confidence: 99%